Teknik Pengenalan Suara Musik Pada Robot Seni Tari - Indra Dwisaputra; Ocsirendi Ocsirendi (Manutech : Jurnal Teknologi Manufaktur, 2018)
The dancing robot has become an annual competition in Indonesia that needs to be developed to improve robot performance. The dancing robot is a humanoid robot that has 24 degrees of freedom. For 2018 the theme raised was "Remo Dancer Robot". Sound processing provides a very important role in dance robots. This robot moves dancing to adjust to the rhythm of the music. The robot will stop dancing when the music is mute. The resulting sound signal is still analogous. Voice signals must be changed to digital data to access the signal. Convert analog to digital signals using Analog Digital Converter (ADC). ADC data is taken by sampling time 254 data per second. The sampling data is stored and grouped per 1 second to classify the parts of Remo Dance music. The results of data classification are in the form of digital numbers which then become a reference to determine the movement of the robot. Robots can recognize conditions when music is in a mute or a play condition.